Improving slaughter hygiene practices for safer pork in Vietnam - International Livestock Research Institute (International Livestock Research Institute, 2020)
The Market-based Approaches to Improving the Safety of Pork in Vietnam (SafePork) Project is working with small-scale pig slaughter facilities in Vietnam to improve pig slaughter processes to ensure consumers have access to safer pork. This video was produced in celebration of the World Food Safety Day 2020. The SafePork project aims to reduce the burden of food-borne disease in informal, emerging and niche markets. It is developing and evaluating light-touch market-based approaches to improving food safety, while safeguarding livelihoods in the pork sector.